Apply Quantitative Management Now - Tarhan, A.; Demirors, O. (IEEE software, 2012)
The Assessment Approach for Quantitative Process Management (A2QPM) helps identify software process measures for quantitative analysis even when organizations lack formal systems for process measurement. A2QPM is the first approach to quantitative management that offers software organizations a well-defined, detailed guideline for assessing their software processes and applying beneficial quantitative techniques to improve them. All the A2QPM applications we've described resulted in quantitative analysis implementations. Although the organizations had institutionalized neither a measurement process nor the processes that were subject to assessment, A2QPM nevertheless enabled quantitative improvement of the issues under study, such as process performance and product quality. Although we didn't intend the approach to be a shortcut for high ML appraisals, it has also helped organizations on their way to high maturity.